2018
DOI: 10.1002/adsc.201700937
|View full text |Cite
|
Sign up to set email alerts
|

Pyrroline Synthesis via Visible‐Light‐Promoted Hydroimination of Unactivated Alkenes with N,N′‐Dimethylpropylene Urea as H‐Donor

Abstract: Synthesis of 3,4-pyrroline derivatives via visible-light-induced hydro/oxyimination of unactivated olefins is reported. In the presence of the photoredox catalyst fac-Ir(ppy) 3 , the key iminyl radical intermediate can be readily generated from O-acyl oximes, and undergoes intramolecular cyclization and H-abstraction from solvent or is trapped by TEMPO to give the corresponding hydro/oxyimination product, respectively. Mechanistic investigations indicate that N,N'-dimethylpropylene urea (DMPU) works as both re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…First, the photoredox SET oxidative generation of iminyl radicals from α ‐imino‐oxy acids were well‐developed as shown by a few elegant examples from the groups of Studer, Leonori, and Liu (Scheme 1A) [5a,h,l,m] . Second, generation of iminyl radicals from the electron‐poor O ‐aryl oximes via SET reduction was exploited by Loh and Xia (Scheme 1B) [5b,i] . Third, Leonori group and Wu group successively showcased that an electron donor‐acceptor complex (EDA), generated from the interaction of 2,4‐dinitro‐substituted aryl oximes with tertiary aliphatic amines, undergoes a SET/fragmentation process upon visible‐light excitation to access the iminyl radicals (Scheme 1C) [5j,n] .…”
Section: Methodsmentioning
confidence: 99%
“…First, the photoredox SET oxidative generation of iminyl radicals from α ‐imino‐oxy acids were well‐developed as shown by a few elegant examples from the groups of Studer, Leonori, and Liu (Scheme 1A) [5a,h,l,m] . Second, generation of iminyl radicals from the electron‐poor O ‐aryl oximes via SET reduction was exploited by Loh and Xia (Scheme 1B) [5b,i] . Third, Leonori group and Wu group successively showcased that an electron donor‐acceptor complex (EDA), generated from the interaction of 2,4‐dinitro‐substituted aryl oximes with tertiary aliphatic amines, undergoes a SET/fragmentation process upon visible‐light excitation to access the iminyl radicals (Scheme 1C) [5j,n] .…”
Section: Methodsmentioning
confidence: 99%
“…Notably, owing to the relatively low bond dissociation energy of S−H bond, thiols are often employed in the photoredox‐catalyzed hydrofunctionalization of alkenes as hydrogen atom relay catalyst without forming C−S bond [12] . On the other hand, to realize the desired thioetherification, oxidative N ‐thiophthalimide has to be used [11d] . With our continuing interest in visible‐light‐promoted difunctionalization of unactivated alkenes, we reported herein an iminothiolation with thiophenols as sulfur donor for the synthesis pyrroline derivatives featuring a thioether substituent (Scheme 1b).…”
Section: Methodsmentioning
confidence: 99%
“…[121] Pyrrolines 125 were synthesized by the irradiation of oxime esters 124 with visible light in the presence of the iridium photoredox catalyst (Scheme 47). [122] The authors suggested that the 5-exo-trig cyclization of the iminyl radical produces the C-centered radical. Product 125 is formed by hydrogen atom transfer from 1,3-dimethyl-1,3-diazinan-2-one (DMPU, solvent) to the C-centered radical.…”
Section: Uv and Visible Light Induced Iminyl Radical Generationmentioning
confidence: 99%